THE INFLUENCE OF ENTREPRENEURSHIP TRAINING ON THE PRODUCTIVITY OF SMES IN SEMARANG CITY, INDONESIA - Suminar, Tri; Yusuf, Amin; Utsman (PEOPLE: International Journal of Social Sciences, 2020)
The SME competition in the globalization era demands business innovation for the competitiveness needed through productive SMEs. The quality of human resources is one of the determining factors of the productivity of SMEs. This study tries to analyze and describe training to improve the productivity of Semarang City SMEs. The research method uses quantitative methods. The study population is a research sample technique using simple random sampling. The number of samples is determined by the Slovin formula, which obtained a valid sample in providing a response that is 171 samples of small and medium assistance that has been obtained entrepreneurship training in the city of Semarang. Data collection using a questionnaire with a Likert scale, while data analysis with descriptive percentages and simple linear regression. The results show that there is a significant positive entrepreneurship training contribution to the productivity of SMEs in the City of Semarang. The contribution of entrepreneurship training to SME productivity was 14.5 percent. Improving the quality of human resources in improving the quality of high-quality competitive products.